Reconstructing Waqf Share Policies: A Maqashid Sharia Approach with Insights from Indonesia - Siddiq, Achmad; Hariyanto; Maula, Ismatul; Meidina, Ahmad Rezy; Arafah, Siti (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2025)
Waqf shares have great potential in supporting social justice, economic empowerment, and sustainable development. However, existing regulations have not been able to fully address the complexity of this instrument. This research analysed and reconstructed the policy of waqf shares in Indonesia through the maqashid sharia approach based on Jasser Auda's system theory. Using qualitative methods through document study and policy analysis, this study examined the compatibility of waqf share policies with the main objectives of sharia, the protection of religion, soul, mind, offspring, and property. The results showed the need for policy reconstruction to establish a waqf share ecosystem that is inclusive and adaptive to modern economic dynamics. Recommendations include strengthening regulations, innovating Islamic financial instruments, and synergising between the government, financial institutions, and religious authorities. The findings contribute to the formulation of a sharia-compatible waqf share policy that is responsive to national socio-economic needs.